Rethinking the identity and economic sustainability of the Church: Case of AOG BTG in Zimbabwe - Kimion Tagwirei; Maake Masango (HTS Teologiese Studies/Theological Studies, 2023)
With burgeoning economic challenges that have been hard-pressing Zimbabwe for more than a decade, most Zimbabwean classical Pentecostal churches who do not strategically multiply their revenue in reciprocal correspondence with God-given resources have been disabled and forced to narrow their missionary focus towards proclamation of the gospel and neglected other dimensions of mission, such as diakonia. The partial focus on the gospel in word without corresponding deeds portrayed an exclusively Salvationist and less integral image, and defaced ecclesiastic identification when Zimbabwe is anxiously in dire need of a wholesome Church that values and attends to all areas of their lives. While extensive attention has been paid to the conceptualisation of ecclesial identity in general, and manipulative economics of some charismatic churches in Zimbabwe and Africa, research about the identity and economic sustainability of the Zimbabwean classical Pentecostal Church is sparse. Thus, this study filled the gap, taking Assemblies of God, Back to God (hereinafter referred to as AOG BTG) as a case study. Applying theonomic reciprocity theory, complemented by the concept of sustainability and engaging purposively sampled in-depth interviews, this article interfaced missionary identity with economic sustainability and recommended the adoption of contextually feasible strategies to capacitate the Church to meet the rising operating and missionary costs in the volatile Zimbabwean context.